The Diverse Subjects of Early Childhood Parenting Education - Schwenker, Vanessa (Social work & society, 2024)
Schwenker explores the concept of diversity by distinguishing between positivist-functionalist and critical approaches. While the positivist-functionalist view treats diversity as fixed personal traits for management and economic purposes, the critical perspective sees diversity as socially constructed through power relations and processes of differentiation. In social work and early childhood education, diversity practices involve categorizing groups for support, but this can risk reinforcing stereotypes, especially around migration. The role of migrant professionals as "bridge persons" highlights tensions between cultural expertise and professional recognition. Adopting a post-structuralist lens, he conceptualizes recognition as an interactive process of "(re-)addressing" that includes selection, normalization, positioning, and valuing. Recognition is not just positive affirmation but can also involve exclusion or disregard, shaping identities relationally and dynamically. This approach emphasizes the fluidity of identities and the norms governing which differences are recognized or ignored in social contexts.